General and robust covalently linked graphene oxide affinity grids for high-resolution cryo-EM - Wang, Feng (Proc Natl Acad Sci U S A, 2020)
Affinity grids have great potential to facilitate rapid preparation of even quite impure samples in single-particle cryo-electron microscopy (EM). Yet despite the promising advances of affinity grids over the past decades, no single strategy has demonstrated general utility. Here we chemically functionalize cryo-EM grids coated with mostly one or two layers of graphene oxide to facilitate affinity capture. The protein of interest is tagged using a system that rapidly forms a highly specific covalent bond to its cognate catcher linked to the grid via a polyethylene glycol (PEG) spacer. Importantly, the spacer keeps particles away from both the air–water interface and the graphene oxide surface, protecting them from potential denaturation and rendering them sufficiently flexible to avoid preferential sample orientation concerns. Furthermore, the PEG spacer successfully reduces nonspecific binding, enabling high-resolution reconstructions from a much cruder lysate sample.